Problematika Kebijakan Pendidikan di Tengah Pandemi dan Dampaknya Terhadap Proses Pembelajaran di Indonesia - Gilang Ramadhan (Student Scientific Creativity Journal, 2023)
The Covid-19 pandemic has changed the whole order of human life, especially the world of education. This requires education to change and adapt quickly to continue the learning process. The purpose of this article is to review the impact of the policy of the Minister of Education and Culture of the Republic of Indonesia regarding Work From Home (WFH) in the world of education. This article was written by reviewing related articles and references regarding online learning policies which are considered as a solution to continue the learning process when schools are closed to prevent the spread of the virus. But on the other hand, this policy has an impact on the process of transforming knowledge for both students, teachers and parents or families.